Evaluation of pain perception during orthodontic debonding of metallic brackets with four different techniques - Delal Dara Kilinç; Gulsilay Sayar (University of São Paulo, 2019)
Abstract Objective The aim of this study was to evaluate patients' pain levels during four different debonding procedures. The null hypothesis was that the pain perception of the patients undergoing four different debonding applications was not statistically significant different. Material and Methods One hundred and twenty orthodontic patients who underwent orthodontic debonding were included in this study. The patients were randomly divided into 4 groups according to technique used in the patients. Debonding groups were as follows: Group 1) Conventional debonding group, Group 2) Medication group (acetaminophen was given 1 hour before debonding), Group 3) Soft bite wax group, and Group 4) Soft acrylic bite wafer group. The patients' levels of anxiety and fear of pain were evaluated before debonding, and Numerical Rating Scale (NRS) was applied to evaluate their pain perception during debonding. Mann-Whitney U and Kruskal-Wallis tests were used to evaluate non-normally distributed data. Categorical data analysis were carried by chi-square and McNemar tests. The significance level was set at p<0.05. Results Anxiety scores of the patients were not statistically significant between both genders and debonding groups. In the quadrants in which the patients were perceived, the highest pain level was in the left side of the mandible. The teeth in which the highest pain level was perceived were the lower left and upper right lateral incisors. Although there was no statistically significant difference among the pain scores of the patients in each group, quadrant scores of female patients showed significant differences, being the lowest scores in the soft bite wax group. Conclusions Majority of the patients had no fear of pain before debonding. Pain levels of the patients in the conventional debonding group were not significantly different from those of the other groups, except quadrant scores of females in the soft bite wax group. The null hypothesis was accepted.